Managing the Security of Sports Stadiums and Their Impact on Consolidating the Values of Citizenship among Fans of Mass Clubs in Baghdad (American Journal of Physical Education and Health Science, 2025)
The security of sports stadiums is the security of human gatherings at all levels, it must have accurate planning based on sound information, the ability to anticipate possible scenarios that may occur in each match, and the preparation to face them in a way that ensures the safety of everyone and does not spoil the pleasure of watching the game. Sports is a luxurious societal image through which the values of good citizenship that society believes in are embodied and reflected on its behaviors inside the stadium. Many times, fans acquire good behaviors inside the stadium that enhance their good values outside the stadium. Therefore, it became necessary to strengthen this behavior through upbringing, organization, and training. Citizenship values are the result of what society believes in, behaviors that determine the actions of its members in a way that enhances social welfare. hence, the importance of research to promote the values of good citizenship through leading the masses in ideal and conscious ways that reflect a civilized image of practicing sports activities. The searcher analyzed the Relationship and impact among the two measures, sports stadium security management and citizenship values, established according to the scientific criteria of pedagogical and psychological scales. The research variables were also evaluated by some members of administrative and technical bodies and Club fan groups in Baghdad. The study reached multiple theoretical and practical results, From her: Statistically significant correlation between the studied variables (security of sports stadiums and citizenship values) and The results of the simple linear regression analysis revealed the existence of significant influence relationships for the independent variable represented by the security of sports stadiums and the dependent variable represented by citizenship values. The researcher recommended that sports clubs should pay attention to training and developing their training and technical staff and their fans ‘ associations to promote the values of citizenship in more modern ways and methods to enhance the spirit of volunteerism and community work.